Early-stage radiological critical analysis of unsuccessful cases following a four-part fracture osteosynthesis of the proximal humerus: focus on the “P” sign - Touloupakis, Georgios; Stuflesser, Wilfried; Ferrara, Fabrizio; Maione, Alessio; Antonini, Guido; Crippa, Cornelio (Acta Biomedica Atenei Parmensis, 2017)
Radiological evaluation of complex intra-articular fractures of the proximal humerus is still challenging. Here, we describe the post-operative “P” sign as a reproducible radiographical mark of a varus reduction, performed by assembling a head-shaft angulation of less than 130 degrees. Our retrospective study was conducted in a group of subjects who previously suffered from proximal humerus four-part fractures. We evaluated the post-operative evolution of specific radiographical parameters that are of crucial prognostic significance: Cervix-diaphysis angle (HHSA), quality level of the orthopaedic reduction (insufficient, sufficient and good) based on a radiological generalized subjective overview, presence of calcar screws through the Philos plate. The final cohort included a group of 39 patients of 70.76 ± 8.3 years of age and an average follow-up of 7.2 months. The post-operative mean HHSA was 131.5 ± 9.4. Interestingly, a positive correlation was detected between presence of the radiographical “P” sign in the post-operative period and the number of surgical complications coming up in the post-operative period (OR: 3.68 - I.C. 95%: 0.7984255-19.2532430), although not statistically significant. In our study, the high number of complications corresponds to literature database. Presence of the “P” sign could be a useful tool for assessing the quality of reduction during intra and post-operative radiological evaluation. We underline the importance of the “P” sign as a “quality of reduction” factor and strongly recommend its intra-operative monitoring as an additional tool together with a standard subjective evaluation of the reduction.